Endocrine therapy with or without whole breast irradiation in low-risk breast cancer patients after breast-conserving surgery: 10-year results of the Austrian Breast and Colorectal Cancer Study Group 8A trial. (March 2020) - Fastner, Gerd; Sedlmayer, Felix; Widder, Joachim; Metz, Martina; Geinitz, Hans; Kapp, Karin; Fesl, Christian; Sölkner, Lidija; Greil, Richard; Jakesz, Raimund; Kwasny, Werner; Heck, Dietmar; et al.
Abstract: Purpose: To investigate long-term results of patients with hormonal receptor–positive breast cancer treated with breast-conserving surgery (BCS) and consecutive endocrine therapy (ET) with or without whole breast irradiation (WBI). Methods and materials: Within the 8 A trial of the Austrian Breast and Colorectal Cancer Study Group, a total of 869 patients received ET after BCS which was randomly followed by WBI (n = 439, group 1) or observation (n = 430, group 2). WBI was applied up to a mean total dosage of 50 Gy (+/− 10 Gy boost) in conventional fractionation. Results: After a median follow-up of 9.89 years, 10 in-breast recurrences (IBRs) were observed in group 1 and 31 in group 2, resulting in a 10-year local recurrence–free survival (LRFS) of 97.5% and 92.4%, respectively (p = 0.004). This translated into significantly higher rates for disease-free survival (DFS): 94.5% group 1 vs 88.4% group 2, p = 0.0156. For distant metastases–free survival (DMFS) and overall survival (OS), respective 10-year rates amounted 96.7% and 86.6% for group 1 versus 96.4% and 87.6%, for group 2 (ns). WBI (hazard ratio [HR]: 0.27, p < 0.01) and tumour grading (HR: 3.76, p = 0.03) were found as significant predictors for IBR in multiple cox regression analysis. Conclusions: After a median follow-up of 10 years, WBI resulted in a better local control and DFS compared with ET alone. The omission of WBI and tumour grading, respectively, were the only negative predictors for LRFS. Highlights: Whole breast irradiation (WBI) significantly improves 10-year local control and disease-free survival in patients with low-risk breast cancer. The omission of WBI and tumour grading were negative predictors for local recurrence–free survival. The benefit of WBI in terms of disease-free survival was not seen after axillary node dissection. No RT effect was detected for overall survival after ten years. For RT de-escalation, biological risk classifications have to be further evaluated.